1997
DOI: 10.1136/bmj.314.7081.629
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant state and mortality from coronary heart disease in lithuanian and swedish men: concomitant cross sectional study of men aged 50

Abstract: Objective: To investigate possible risk factors and mechanisms behind the four times higher and diverging mortality from coronary heart disease in Lithuanian compared with Swedish middle aged men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
3
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 31 publications
3
75
3
2
Order By: Relevance
“…The alcohol intake was similar in the 2 study populations. 4 The finding that the Lithuanian population with a high risk for cardiovascular disease has a lower plasma ␥-tocopherol level is also interesting in relation to a recent report that CHD patients have reduced serum levels of ␥-but not ␣-tocopherol. 24 Although ␥-tocopherol is less efficient as an antioxidant compared with ␣-tocopherol, it has been shown to be superior in detoxifying nitrogen dioxide.…”
Section: Discussionmentioning
confidence: 55%
“…The alcohol intake was similar in the 2 study populations. 4 The finding that the Lithuanian population with a high risk for cardiovascular disease has a lower plasma ␥-tocopherol level is also interesting in relation to a recent report that CHD patients have reduced serum levels of ␥-but not ␣-tocopherol. 24 Although ␥-tocopherol is less efficient as an antioxidant compared with ␣-tocopherol, it has been shown to be superior in detoxifying nitrogen dioxide.…”
Section: Discussionmentioning
confidence: 55%
“…This leads to a lower ratio of a-to g-tocopherol after the RO diet compared to the SAT diet. A low g-tocopherol concentration and a high a-to g-tocopherol ratio has been reported in patients with CHD compared to controls Kontush et al, 1999) and in a population with a high incidence of CHD (Kristenson et al, 1997). These results suggest that a serum tocopherol profile with low g-tocopherol levels and a high a-to g-tocopherol ratio may be an indicator of an increased risk for CHD and that rapeseed oil-rich diets may help to increase the levels of g-tocopherol in the body.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, we found that plasma levels of carotenoids in Czech middle aged men were about half of those in Bavaria and Israel (Bobak et al, submitted for publication). A recent study comparing Swedish and Lithuanian men reported that Lithuanians had signi®cantly lower levels of several carotenoids, as well as lower resistance of low density lipoprotein to oxidation (Kristenson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%